Ecology and restoration potential of Ruppia maritima in a managed mosquito impoundment of the Indian River Lagoon, Florida, USA - Deanna F. Webber; Richard E. Mulroy; Patrick H. Monaghan; David C. Heuberger; M. Dennis Hanisak; Rachel A. Brewton (Regional Studies in Marine Science, 2026)

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Ecosurveillance reveals subtle metabolic effects on the non-native cane toad (Rhinella marina) from low levels of accumulated environmental per- and polyfluoroalkyl substances - Damian C. Lettoof; Marina Suzuki; Sandra Nilsson; Thao V. Nguyen; Nicholas Bourne; Cassandra L. Pegg; Sally Stockwell; Utpal Bose; Jacob Devine; Tyler Contor; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

A techno-economic review of direct air capture of moisture processes: sustainable versus energy-intensive methods - M. Webber; A. Aliyu; S.-H. Jin; M. M. Sadiq; B. Sohani; A. Elseragy (International Journal of Environmental Science and Technology, 2025)
One of the biggest challenges that the world faces today is the availability of fresh and potable water in arid, semi-arid, and deprived regions. This is a challenge that concerns not only economic development but also social development spanning several UN SDGs. This article presents a detailed critical and systematic review of the technologies for producing industrial and potable water. Emphasis is made on direct air capture (DAC) methods as the next frontier in sustainable water production against the backdrop of traditional energy intensive methods such as desalination. Comparisons using a variety of techno-economic, scale, geographic, and environmental metrics are carried out. While market reports suggest that investments and market value of DAC technologies will continuously rise, these data only extend the next 5–10 years. However, using this data, a projection was made by the authors on various scenarios leading to 2050. At 2030, best projections fall short of UN SDG 6 predictions for a four-fold increase (from 2020 levels) required to sustain populations. The review notes that DAC has the potential to be an attractive solution for the current water crisis (in some cases drought) experienced in various regions on earth. The report finds that while several moisture DAC technologies (e.g., fog and dew water harvesting) are currently being developed, they are only being implemented on small scales around the world—with huge implications for arid and deprived regions of the world.

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Scientific agenda for climate risk and impact assessment of West African cropping systems - M. Diancoumba; D. MacCarthy; H. Webber; F. Akinseye; B. Faye; F. Noulèkoun; A. Whitbread; M. Corbeels; N. Worou (Global Food Security, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Ruchira Somaweera; Vinay Udyawer; Michael L. Guinea; Daniela M. Ceccarelli; Rohan H. Clarke; Michelle Glover; Mathew Hourston; John Keesing; Arne Redsted Rasmussen; Kate Sanders; Richard Shine; Damian P. Thomson; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Tree pests and diseases: the threat to biodiversity and the delivery of ecosystem services - Peter H. Freer-Smith; Joan F. Webber (Biodiversity and Conservation, 2017)

Color patterns in white‐beaked dolphins ( Lagenorhynchus albirostris ) from Iceland - Chiara G. Bertulli; Anders Galatius; Carl C. Kinze; Marianne H. Rasmussen; William Keener; Marc A. Webber (Marine Mammal Science, 2016)
Few studies have examined the natural complex pigmentation patterns of white‐beaked dolphins. From 2002 to 2014, whale‐watching trips in Iceland provided a platform of opportunity to collect a large body of photographs of free‐ranging individuals from a single area of distribution for this species. Based on 823 images, 571 individuals showing one or more color components were identified, and assigned to the following four age classes: adults ( n = 437), juveniles ( n = 109), calves ( n = 14), and neonates ( n = 11). A total of 26 color components were observed and described: seven terms previously applied to white‐beaked dolphins, 12 previously applied to other dolphin species, and seven newly defined terms. Results showed that each age class could be positively identified by differences in specific color components, some of which were exclusive. Therefore, color patterns may prove useful in estimating maturity in free‐ranging white‐beaked dolphins. This tool could be further refined through assessment of a wide sample of freshly stranded specimens of known sex and age, which could reveal new age class‐specific components, as well as sexually dimorphic characteristics not seen here. Geographic variation should be investigated by comparing image data sets and stranded animals from different parts of the North Atlantic.

Social network characteristics and predicted pathogen transmission in summer colonies of female big brown bats (Eptesicus fuscus) - Quinn M. R. Webber; R. Mark Brigham; Andrew D. Park; Erin H. Gillam; Thomas J. O’Shea; Craig K. R. Willis (Behavioral Ecology and Sociobiology, 2016)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

A Framework to Report the Production of Renewable Diesel from Algae - Colin M. Beal; Colin H. Smith; Michael E. Webber; Rodney S. Ruoff; Robert E. Hebner (BioEnergy Research, 2011)

Adapting the CROPGRO model for saline soils: the case for a common bean crop - H. A. Webber; C. A. Madramootoo; M. Bourgault; M. G. Horst; G. Stulina; D. L. Smith (Irrigation Science, 2010)

Molecular characterisation of two novel double-stranded RNA elements from Phlebiopsis gigantea - Zisis Kozlakidis; Caroline V. Hacker; Dominic Bradley; Atif Jamal; Xiyu Phoon; Joan Webber; Clive M. Brasier; Kenneth W. Buck; Robert H. A. Coutts (Virus Genes, 2009)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

High irradiance increases organogenesis in friable callus of Caustis blakei Kük. (Cyperaceae) - Julie Webber; Margaret E. Johnston; Alan H. Wearing (In Vitro Cellular & Developmental Biology - Plant, 2003)

The protective effects of hypoxia-induced hypometabolism in the Nautilus - R. G. Boutilier; T. G. West; D. M. Webber; G. H. Pogson; K. A. Mesa; J. Wells; M. J. Wells (Journal of Comparative Physiology B, 2000)

Capillary Imbibition and Pore Characterisation in Cement Pastes - A. Leventis; D. A. Verganelakis; M. R. Halse; J. B. Webber; J. H. Strange (Transport in Porous Media, 2000)

Applications and performance of Radio-Acoustic Positioning and Telemetry (RAPT) systems - R. K. O'Dor; Y. Andrade; D. M. Webber; W. H. H. Sauer; M. J. Roberts; M. J. Smale; F. M. Voegeli (Hydrobiologia, 1998)

Lumbar paraspinal muscle fatigability in repetitive isoinertial loading: EMG spectral indices, Borg scale and endurance time - Markku Kankaanp; Simo Taimela; Charles L. Webber; Olavi Airaksinen; Osmo Hnninen (European Journal of Applied Physiology, 1997)

Heterogeneity of the hemoglobin of the Ohrid trout (Salmo L. typicus) - Biljana Cepreganova; Jerry B. Wilson; Brooke B. Webber; Biljana Kjovkareska; Georgi D. Efremov; Titus H. J. Huisman (Biochemical Genetics, 1992)

HTLV-I antibody studies in villagers in East Sepik Province, Papua New Guinea - R. C. Sanders; A. Levin; G. Anian; I. Webber; H. Lee; P. Swanson; A. Diwan; R. Desowitz; W. A. Blattner; M. P. Alpers (Archives of Virology, 1990)

?-Thalassemia and the production of different ? chain variants in heterozygotes - A. E. Felice; B. B. Webber; T. H. J. Huisman (Biochemical Genetics, 1981)